Evaluation of an innovative nurse educational programme of nurse education - Hartley, Mavis E. (1996)
In 1984 the English National Board (the newly appointed controlling body for nurse education in England) invited schools of nursing to submit innovatory and progressive programmes for nurse education. Basis for selection was the capacity of the programmes to begin to address the demands for a new type of nursing practitioner. The programmes were to be aimed at providing an education that would enable the nurse of the future to adapt to the changing needs created by an increasingly dynamic nursing profession. It was proposed that the selected programmes would act as forerunners for new educational initiatives and facilitate the transition to a more clearly oriented nursing approach.